PENERAPAN METODE MIND MAPPING BERBANTUAN SPSS PADA MATAKULIAH STATISTIKA PENDIDIKAN - Trimurtini Trimurtini; Wahyuningsih Wahyuningsih; Nursiwi Nugraheni; Sri Susilaningsih (JURNAL LITBANG PROVINSI JAWA TENGAH, 2016)
The purpose of this study is (1) to describe the implementation of SPSS-assisted mind-mapping method in the subject of Education Statistics; (2) to compare the results of student learning in a class learning using SPSS-assisted mind-mapping method and using other method for the subject of Education Statistics. This study uses a mixed method of qualitative and quantitative research. The conclusions of this study are (1) the steps in the implementation of SPSS-assisted mind-mapping method start with problem posing, group discussions, presentations, drawing conclusions, and practice of processing data with SPSS; and (2) the results of student learning in a class learning using SPSS-assisted mind-mapping method is better than the results of student learning in the class using other methods.